TRANSMISSIBLE DRUG RESISTANCE, PLASMID CHARACTERIZATION IN SHIGELLA AND SALMONELLA, AND VIRULENCE OF SHIGELLA ISOLATED FROM DIARRHOEIC HUMANS AND PIGLETS (1990)
A total of 10,200 faecal samples including 10,000 from diarrhoeic human beings and 200 from diarrhoeic piglets were collected. The human faecal samples were collected from the three government hospitals in Ibadan, namely: The University College Hospital, State Hospitals at Adeoyo and Ring Road, while the piglets were on the Teaching and Research Farm, of the University of lbadan. Thirty Shigella and twenty-two Salmonella spp. were isolated from the human faecal samples while one Shigella isolate was obtained from the faecal samples of piglets. The Shigellae were sero1ogically identified as S. E1exneri (23 from humans and 1 from a piglet), s. dysenteriac (4 isolates from human) and S. boydii (3, all were isolated from human). Of the Salmonella isolates, 9 were identified as S.typhi while the remaining 13 were classified as Salmonella species. One microgram per ml potassium tellurite in MacConkey agar was used to enhance the isolation of Shigellae. Antimicrobial susceptibi1ity testing to eight antibiotics were performed on the fifty-three bacterial isolates. Twenty-one antibiotic resistance patterns were identified. The highest pattern T-CT-F-A-S-C-Te (Septemdrip1e) was found in eleven isolates, sextiple resistant pattern in thirteen; quintiple pattern in eight isolates; quadriple in four isolates; triple in eight isolates; double in four isolates while resistance to single antibiotic (Te and CT) was found in five bacterial isolates. The Minimal Inhibitory Concentrations (MIC) of 4 antibiotics (ampicillin, ch1oramphenico1, Streptomycin and tetracyc1ine) were determined for the bacterial isolates. Two of the Shigella isolates were sensitive to ampicillin, the MIC of ampicillin was 8 ug per ml for them, 1 to chloramphenicol; 4 to streptomycin while all isolates were resistant to tetracyc1ine. The MIC of ampicillin for 14 of the Salmonel1a isolates was 8 ug per ml while 11 and 9 isolates of the same organism: were resistant to chloramphenicol and Streptomycin respective1y. The following resistance patterns were observed: A-C-S-T, C-S-T, A-C-T and A-S-T. All the forty-two isolates screened transferred ampicillin resistance (100 percent). Twenty-one isolates (50.0 percent) transferred two determinants, either A-T or A-S or A-C. Seven (16.6 percent) transferred three determinants either A-T-S or A-S-C. None of the isolates transferred four determinants (A-T-S-C). Among the Shigela isolates the chloramphenicol determinant was transferred at a low frequency (only 3 of the 28 screened) whereas the Salmonella isolates transferred at a higher frequency (6 of the 14 screened). The R plasmids range in size between 2.2 to 38.0 Mdal. The chloramphenicol R plasmid has a molecular weight of 4.00 Mdal., streptomycine 38.0 Mdal. The plasmid profile of the isolates was also investigated using agarose gel lectophoresis method. The Shigella isolates exhibited a large number of small cryptic plasmids. In contrast, the Salmonella isolates exhibited fewer number of plasmids. All the plasmids range between 0.8 and 55.5 Mdal in size. The virulence of the Shigella isolates was investigated using Sereny Test and Rabbit ligated ileal loop test. Four of the fourteen Shigelle isolates including S. Flexneri (2), S. boydii (1), S. dysenteriae (1) produced Keraconjuctivities in guinea pigs. Six of the Shigella isolates including four S. flexneri, one S. dysenteriae and one S.boydii dilated ligated ligate rabbit ilea loop with accumulation of fluid. Histological ulterations foun in the ilea loops exposed to these enterotoxins included inflammation, general degeneration, submucosal oedema and neutrophilic infiltrations. Four of the Shigella isolates comprising of two S.flexneri, one S. dysenteriae and one S. boydii dilated the ligated intestinal loop of rabbit with accumulation of fluid when enterotoxin heated at 65 C for 30 min. were used. It was observed for the first time that the S. boydii produced heat labile and heat stable enterotoxin in ligated rabbit illeal loop. Oral inoculation of the invasive Shigella isolates into pretreated (starved and calcium carbonate treated) mice and guinea pigs failed to produce clinical manifestation of dysentery-like diarrhoea and febrile condition.